2014
DOI: 10.1039/c3cp54955k
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition from supercritical fluids

Abstract: Recent studies have shown that it is possible to electrodeposit a range of materials, such as Cu, Ag and Ge, from various supercritical fluids, including hydrofluorocarbons and mixtures of CO2 with suitable co-solvents. In this perspective we discuss the relatively new field of electrodeposition from supercritical fluids. The perspective focuses on some of the underlying physical chemistry and covers both practical and scientific aspects of electrodeposition from supercritical fluids. We also discuss possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 128 publications
1
36
0
3
Order By: Relevance
“…Organic co-solvents form a single phase with scCO 2 and considerably improve the solubility of ionic species. This mixed solvent phase has been largely documented in the field electrodeposition [3,18,22], with Bartlett et al recently reviving interest in SCFs as electroplating media. Their research efforts have demonstrated that the unique mass transport properties and lack of surface tension in supercritical media permit the formation of well-defined nano-structured electrodeposits [3].…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 99%
See 3 more Smart Citations
“…Organic co-solvents form a single phase with scCO 2 and considerably improve the solubility of ionic species. This mixed solvent phase has been largely documented in the field electrodeposition [3,18,22], with Bartlett et al recently reviving interest in SCFs as electroplating media. Their research efforts have demonstrated that the unique mass transport properties and lack of surface tension in supercritical media permit the formation of well-defined nano-structured electrodeposits [3].…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 99%
“…This mixed solvent phase has been largely documented in the field electrodeposition [3,18,22], with Bartlett et al recently reviving interest in SCFs as electroplating media. Their research efforts have demonstrated that the unique mass transport properties and lack of surface tension in supercritical media permit the formation of well-defined nano-structured electrodeposits [3]. Other electrochemically driven reactions of interest studied in this mixed solvent phase are electrocarboxylation of benzyl chloride [23] and conducting polymer synthesis [24,25].…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the cell and position of the electrodes. The dry electrolytes were weighed into the cell (described elsewhere [13,22]) in the atmosphere and this was then transferred to the glove box anti-chamber. After 15 h under nitrogen flow the cell was assembled inside the glove box where the dry acetonitrile co-solvent was added.…”
Section: Introductionmentioning
confidence: 99%